Effects of prior knowledge and collaborations on R&D performance in times of urgency: the case of COVID-19 vaccine development - Daniel Laufs; Tetyana Melnychuk; Carsten Schultz (R&D Management, 2024)
Innovation usually requires time-consuming exploratory approaches. However, external shocks and related crises, such as the COVID-19 pandemic, lead to severe time pressures, which require short-term R&D results. We investigate how organizations' prior collaboration and existing knowledge not only helped them cope with the crisis but also affected the vaccine's development performance. Specifically, we investigate the R&D outcomes of 386 organizations involved in the COVID-19 vaccine's development within the first 180.167emmonths after the pandemic's outbreak. The results reveal that under urgency, organizations with prior scientific collaborations and technological knowledge exhibit a higher R&D performance. Furthermore, a broad network of diverse collaborators strengthened this relationship, thereby calling for more interdisciplinary R&D activities. We therefore extend the literature on innovation speed and strengthen long-term R&D outcomes' role in organizations with a broad existing knowledge base and collaboration networks. We do so by specifically supporting such organizations' ability to integrate their previous R&D's and collaborations' knowledge to achieve rapid innovative outcomes under urgency.
Keywords: 650